Análise estrutural da importina-α de MUS MUSCULUS complexada a sequência de localização nuclear do fator de transcrição PAC-3 - Silva, Tainá Dorte da [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The eukaryotic cells have a membrane that separates the nucleus and cytoplasmic compartments, through which the transport of macromolecules occurs. In this process, macromolecules with more than 60 KDa cross the nuclear pore complex (NPC) with the aid of selective receptors, which specifically recognize the protein to be transported from one compartment to another. Mus musculus Importin-α, (MmImpα) is one of these receptors, and acts on the recognition of nuclear localization sequences (NLS) of the proteins that will be imported into the nucleus. Impα recognizes the NLSs and, with the aid of Importin-β (Impβ), which mediates the interaction of the complex with the NPC, transports them into the nucleus by forming a heterodimer (Impα / Impβ). This mechanism is known as the Classical Import Way of nuclear. This work aims to study the interaction of the NLS complex of the PAC-3 protein, characteristic of the fungus Neurospora crassa, with MmImpα, in order to compare the interaction of the same NLS with different Impα. The complex was subjected to different experiments after the expression and purification of the protein, such as Isothermal Titration Calorimetry (ITC), to measure the interaction and obtain the thermodynamic constants, and the co-crystallization. The ITC showed that the NLS peptide interaction of PAC-3 protein with MmImpα occurs with high affinity. After crystallization, the best crystal was subjected to X-ray diffraction and collected at a resolution of 2.17 Ǻ. The elucidation of the MmImpα/NLS-PAC-3 complex showed electronic density at the two sites of Impα interaction, main (S1) and secondary (S2), but not in the linker region. Thus, based on the electronic densities, it was possible to model a C-terminal portion of the peptide at both MmImpα sites. This work shows that the NLS-PAC-3 peptide interacts with MmImpα in a monopartite, non-bipartite manner as suggested in previous studies and does not follow the classical consensus of NLSs interaction with Impα, therefore, the NLS sequence belonging to PAC-3 protein can be considered a non-classical monopartite NLS

As células eucariontes possuem uma membrana que separa os compartimentos núcleo e citoplasma, pela qual ocorre o transporte de macromoléculas. Nesse processo, as macromoléculas com mais de 60 KDa atravessam o complexo poro nuclear (NPC) com o auxílio de receptores seletivos, os quais reconhecem especificamente a proteína a ser transportada de um compartimento para outro. A Importina-α de Mus musculus, (MmImpα) é um desses receptores, e atua no reconhecimento de sequências de localização nuclear (NLS) das proteínas que serão importadas para o núcleo. A Impα reconhece as NLSs e com o auxílio da Importina-β (Impβ), a qual media a interação do complexo com o NPC, as transporta para o interior do núcleo pela formação de um heterodímero (Impα/Impβ). Esse mecanismo é conhecido como Via Clássica de Importação nuclear. Este trabalho tem como objetivo estudar a interação do complexo formado pela NLS da proteína PAC-3, característico do fungo Neurospora crassa, com a MmImpα, afim de comparar a interação de um mesmo NLS com diferentes Impα. O complexo foi submetido à diferentes experimentos após a expressão e purificação da proteína, como Calorimetria de Titulação Isotérmica (ITC), para medir a interação e obter as constantes termodinâmicas, e co-cristalização. O ITC mostrou que a interação do peptídeo NLS da proteína PAC-3 com a MmImpα ocorre com alta afinidade. Após a cristalização, o melhor cristal foi submetido a difração de raios X e coletado com resolução de 2,17 Ǻ. A elucidação do complexo MmImpα/NLS-PAC-3 mostrou densidade eletrônica nos dois sítios de interação da Impα, principal (S1) e secundário (S2), porém não na região de linker. Assim, baseado nas densidades eletrônicas, foi possível modelar uma porção C-terminal do peptídeo em ambos os sítios da MmImpα. Esse trabalho nos mostra que o peptídeo NLS-PAC-3, interage com a MmImpα de forma monopartida, e não bipartida como sugerido em estudos anteriores e não segue o consenso clássico de interação de NLSs com a Impα, portanto, a sequência NLS pertencente a proteína PAC-3 pode ser considerada um NLS monopartido não-clássico
Keywords: Importina-α; Localização nuclear; NLS; PAC-3